Modern Chemical Routes for the Controlled Synthesis of Anisotropic Bimetallic Nanostructures and Their Application in Catalysis - Bhol, Prangya; Bhavya, M. B.; Swain, Swarnalata; Saxena, Manav; Samal, Akshaya K. (Frontiers in Chemistry, 2020)
Bimetallic nanoparticles (BNPs) have attracted widespread attention compared to monometallic counterpart because of their chemical/physical properties. The BNPs have wide range of applications in the field of health, energy, water and environment. These properties could be tuned with number of parameters such as compositions of the bimetallic systems, their preparation method, and morphology. Monodisperse and anisotropic BNPs have gain the considerable interest and numerous efforts have been made for the controlled synthesis of bimetallic nanostructures of different size and shape. This review emphasize a brief summary over the various synthetic routes adopted for the synthesis of Palladium(Pd), Platinum(Pt), Nickel(Ni), Gold(Au), Silver(Ag), Iron(Fe), Cobalt(Co), Rhodium (Rh) and Copper(Cu) based transition metal bimetallic anisotropic nanostructures, accepted growth mechanisms e.g. seed mediated co-reduction, hydrothermal, galvanic replacement reactions, and antigalvanic reaction and their application in the field of catalysis. Effect of surfactant, reducing agent, metal precursors ratio, pH, and reaction temperature for the synthesis of anisotropic nanostructures has been explained with examples. This review further discusses how slight modifications in one of the parameters alter the growth mechanism resulting different anisotropic nanostructures. The progress or modification implied in the synthesis techniques within recent years is focused in this article. Furthermore, this article discussed the improved activity, stability and catalytic performance of bimetallic nanostructures compared to the monometallic performance. The synthetic strategies reported here shed the deeper understanding of mechanism and development of sophisticated and controlled bimetallic nanostructures for enormous application.